A Psychiatrist's Duties in Relation to the Risks of Patient Suicide Smith v Pennington [2015] NSWSC 1168 (Garling J). Issue 1 (2nd January 2016) - Freckelton QC, Ian; Scott, Russ
Abstract : In November 2008, after making a serious attempt to commit suicide by hanging, a 25-year-old single man was made subject to an involuntary treatment order pursuant to the Mental Health Act 2007 (NSW). After a six-day admission to a mental health unit, he was granted four nights of leave from a hospital mental health unit to his parents' home. He attempted suicide by hanging again and sustained catastrophic injuries. He took legal action, claiming that either the grant of leave or the manner of the grant of leave was negligent and that had he remained in the hospital mental health unit, he would not have attempted to harm himself. In a lengthy judgment, Smith v Pennington [2015] NSWSC 1168, Garling J considered the issues of breach of duty of care and the higher threshold of the duty of care pursuant to the special statutory powers of section 43 of the Civil Liability Act 2002 (NSW) as well as foreseeability, reasonableness of precautions and causation. In a judgment that should be cautionary to plaintiffs in 'failure to warn' claims against psychiatrists and hospitals, Garling J held that the plaintiff had not proved that any negligence had caused his injuries, dismissed the action and ordered the plaintiff to pay the defendants' costs.